Selection of Naturally Occurring Extended-Spectrum TEM β-Lactamase Variants by Fluctuating β-Lactam Pressure - Blazquez, Jesús (American Society for Microbiology, 2000)
Despite the large number of in vitro mutations that increase resistance to extended-spectrum cephalosporins in TEM-type β-lactamases, only a small number occur in naturally occurring enzymes. In nature, and particularly in the hospital, bacteria that contain β-lactamases encounter simultaneous or consecutive selective pressure with different β-lactam molecules. All variants obtained by submitting an Escherichia coli strain that contains a bla(TEM-1) gene to fluctuating challenge with both ceftazidime and amoxicillin contained only mutations previously detected in naturally occurring β-lactamases. Nevertheless, some variants obtained by ceftazidime challenge alone contained mutations never detected in naturally occurring TEM β-lactamases, suggesting that extended-spectrum TEM variants in hospital isolates result from fluctuating selective pressure with several β-lactams rather than selection with a single antibiotic.